Preparation of magnetically recyclable CuFe2O4/RGO for catalytic hydrolysis of sodium borohydride. (10th August 2016) - Tang, Mingyi; Xia, Fengling; Gao, Chunjuan; Qiu, Haixia
Abstract: CuFe2 O4 /reduced graphene oxide (RGO) nanostructures were fabricated by a facile chemical method, and the shape and size of the CuFe2 O4 nanoparticles were tuned through changing the concentration of the reactants and the reaction temperature. The CuFe2 O4 /RGO nanostructures were firstly analyzed by transmission electron microscopy, Fourier Transform infrared spectroscopy and powder X-ray diffraction, and then they were exploited as magnetically recyclable catalyst for the hydrolytic dehydrogenation of NaBH4 for hydrogen evolution. They exhibited superior catalytic activity and recyclability. The calculated activation energy was 33.95 kJ mol −1, which is even lower than some metallic nanoparticle catalysts. So the CuFe2 O4 /RGO nanostructures will find potential applications as magnetically recyclable catalysts in hydrogen storage system for fuel cell applications. Highlights: The as-prepared CuFe2 O4 /RGO exhibited excellent catalytic performance toward catalytic hydrolysis of NaBH4 . The TOF value is 1.7 mol H2 min −1 (mol Cu) −1 for the catalytic hydrolysis of NaBH4, and activity factor (33.95 kJ mol −1 ). The catalytic performance of CuFe2 O4 /RGO was even lower than some noble metal nanoparticles.